MINUMAN BERKALORI DAN KONTRIBUSINYA TERHADAP TOTAL ASUPAN ENERGI REMAJA DAN DEWASA - Ni Made Putria Sukma Febriyani; . Hardinsyah; Dodik Briawan (Jurnal Gizi dan Pangan, 2012)
The objective of this research was to analyze energy intake from calorie beverages (EICB) and it’s contribution to the total energy intake of adolescents and adults. The research was carried out through analyzing a data set of THIRST (The Indonesian Regional Hydration Study) collected in 2008 and 2009 by applying a crossectional study design among 606 adolescents (male and female aged 15-18 yrs) and 594 adults (male and female aged 25-55 yrs) in North Jakarta, West Bandung, Surabaya, Malang, Makasar and Malino. Data processing and analysis were conducted in Bogor in April-June 2011. The results showed that the mean EICB among adolescents was 420 ± 406 kcal/day and among adults was 450 ± 382 kcal/day, which is 21.2% and 23.4% of the total energy intake (TEI) of adolescents and adults respectively. EICB was moderately associated with TEI of adolescents (r= 0.58)